Upaya Meningkatkan Hasil Belajar Matematika Materi Membaca Jam dengan Metode Demonstrasi melalui Media Jam Analog pada Siswa Kelas III Sekolah Dasar - Taspiyah, Taspiyah (Universitas Sebelas Maret, 2022)
This research aims to improve the mathematics learning outcomes of class III students at SD Negeri 1 Kiringan in 2022 through analog clocks. This research uses a classroom action research design with the Arikunto model (2013: 17). The research subjects were class III students at SD Negeri 1 Kiringan, totaling 6 students. The object of the research is the results of learning mathematics, reading clock material using analog clock media. Data collection instruments use observation sheets and tests. Data analysis techniques using quantitative descriptive analysis and qualitative descriptive analysis. Based on the results obtained, it can be concluded that the increase in learning outcomes for reading clock material using analog clock media for class III students at SD Negeri 1 Kiringan has increased. The results of the research showed that the average class score in cycle I was 70.83, while in cycle II the class average reached a score of 90 with good criteria and everything was completed. In this way, students can read the clock using an analog clock according to the correct rules.